Presence of Spotters Improves Bench Press Performance: A Deception Study. Issue 7 (July 2019) - Sheridan, Andrew; Marchant, David C.; Williams, Emily L.; Jones, Hollie S.; Hewitt, Phil A.; Sparks, Andy
Abstract : Abstract: Sheridan, A, Marchant, DC, Williams, EL, Jones, HS, Hewitt, PA, and Sparks, SA. Presence of spotters improves bench press performance: a deception study. J Strength Cond Res 33(7): 1755–1761, 2019—Resistance exercise is a widely used method of physical training in both recreational exercise and athletic populations. The use of training partners and spotters during resistance exercise is widespread, but little is known about the effect of the presence of these individuals on exercise performance. The purpose of the current study was to investigate the effect of spotter presence on bench press performance. Twelve recreationally trained participants (age, 21.3 ± 0.8 years, height, 1.82 ± 0.1 m, and mass, 84.8 ± 11.1 kg) performed 2 trials of 3 sets to failure at 60% of 1 repetition maximum on separate occasions. The 2 trials consisted of spotters being explicitly present or hidden from view (deception). During the trials, total repetitions (reps), total weight lifted, ratings of perceived exertion (RPE), and self-efficacy were measured. Total reps and weight lifted were significantly greater with spotters (difference = 4.5 reps, t = 5.68, p < 0.001 and difference = 209.6 kg, t = 5.65, p < 0.001, respectively). Although RPE and local RPE were significantly elevated in the deception trials (difference = 0.78, f = 6.16, p = 0.030 and difference = 0.81, f = 5.89, p = 0.034, respectively), self-efficacy was significantly reduced (difference = 1.58, f = 26.90, p < 0.001). This study demonstrates that resistance exercise is improved by the presence of spotters, which is facilitated by reduced RPE and increased self-efficacy. This has important implications for athletes and clients, who should perform resistance exercise in the proximity of others, to maximize total work performed.